The Use of Translanguaging in Bilingual Class: A Study of Perception on the Students at An Islamic Junior High School - Antika, Rindi; Jabu, Baso; Sakkir, Geminastiti (Journal for Teaching and Education for Scholars, 2026)
While translanguaging is increasingly recognized as a pedagogical tool, its implementation in the specific context of Islamic bilingual junior high schools remains under-explored, particularly from the students' perspective. This study investigates how students at SMP IT Al-Biruni Mandiri Jipang perceive and interpret translanguaging in their bilingual classrooms. Using a descriptive qualitative approach, data were gathered through three days of classroom observations and in-depth interviews with six seventh-grade students, then analyzed using the interactive model of Miles and Huberman (1994). The findings reveal that students perceive translanguaging as a vital "cognitive bridge" that facilitates the understanding of complex material, reduces foreign language anxiety, and promotes active participation. Specifically, students identified a preference for strategic language switching that differentiates between social interaction and formal teacher-led instruction . Although students acknowledge the pedagogical benefits of L1 support, they also emphasize the need for judicious implementation to prevent over-reliance and maintain sufficient English exposure. These findings highlight the importance of designing responsive bilingual teaching strategies that incorporate student voices to optimize foreign language acquisition.